Binding pancreaticogastrostomy anastomosis in central pancreatectomy: A single center experience. Issue 45 (November 2017) - Kang, Pengcheng; Wang, Zhidong; Leng, Kaiming; Zhong, Xiangyu; Wang, Hao; Wan, Ming; Tai, Sheng; Cui, Yunfu
Abstract : Abstract: A growing number of central pancreatectomies are performed. However, reconstruction of pancreaticoenteral digestive continuity after central pancreatectomy remains debated. This study evaluates the short-term outcomes of binding pancreaticogastrostomy anastomosis in central pancreatectomy. We have reviewed our experience with 52 patients who underwent binding pancreaticogastrostomy following central pancreatectomy from February 2009 to March 2015. Indication includes 6 noninvasive intraductal papillary mucinous neoplasms, 11 neuroendocrine tumors, 12 solid pseudopapillary tumor, 9 serous cystadenoma, 6 mucinous cystadenoma, and 8 focal pancreatic traumas. The mortality rate was nil while the morbidity rate was 34.6%. Eighteen patients experienced complications including 6 pancreatic fistulas, 2 postpancreatectomy hemorrhages, 4 delayed gastric emptying, 1 hypostatic pneumonia, and 5 pancreatitis. The median postoperative length of hospital stay was 12 days (10 days for patients without fistula). None of the 52 patients were found to have pancreatic endocrine or exocrine insufficiency or recurrence of tumors. Central pancreatectomy with binding pancreaticogastrostomy is a useful and practicable surgical procedure for benign or borderline lesions of the pancreatic neck or proximal body. Abstract : Supplemental Digital Content is available in the text